The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/hep.32139
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma differentiation—Associated gene 5 protects against NASH in mice

Abstract: Background and Aims: NASH is a complicated disease characterized by hepatocyte steatosis, inflammation infiltration, and liver fibrosis. Accumulating evidence suggests that the innate immunity plays a key role in NASH progression. Here, we aimed to reveal the role of melanoma differentiation-associated gene 5 (MDA5, also known as Ifih1), a conventional innate immune regulator following viral infection, in the progression of NASH and investigate its underlying mechanism. Approach and Results:We first examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Three well-characterized MAPK subfamilies are p38, JNK, and ERK1/2, which are related to NASH development. MAPK can be activated by upstream kinase signals, such as apoptosis signal-regulated kinase 1 and mixed-spectrum kinase 3 34,35 . By contrast, MAPKs are inactivated through direct dephosphorylation of their threonine and tyrosine residues by a set of bispecific protein tyrosines [36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…Three well-characterized MAPK subfamilies are p38, JNK, and ERK1/2, which are related to NASH development. MAPK can be activated by upstream kinase signals, such as apoptosis signal-regulated kinase 1 and mixed-spectrum kinase 3 34,35 . By contrast, MAPKs are inactivated through direct dephosphorylation of their threonine and tyrosine residues by a set of bispecific protein tyrosines [36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…ASK1 is a mitogen‐activated protein kinase kinase kinase (MAP3K), and widely expressed in tissue and cells that regulates the MAPK pathways through homodimerization and subsequent autophosphorylation in response to stressful stimuli from various sources including ROS, endoplasmic reticulum stress, bacterial and viral infections, calcium inward flow, and inflammatory signals 33 . Numerous studies have demonstrated that overactivation of the ASK1/JNK/p38 pathway in the liver of NASH plays an important role in disease progression and that inhibition of ASK1 attenuates insulin resistance, inflammation and hepatic lipid accumulation in NASH 35–38 . Although some clinical trials on the treatment of NASH with small molecule inhibitors of ASK1 have not reached definitive endpoints yet, the current efforts of the researchers to treat NASH and its related complications by interfering with ASK1 have never been stopped 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…33 Numerous studies have demonstrated that overactivation of the ASK1/JNK/p38 pathway in the liver of NASH plays an important role in disease progression and that inhibition of ASK1 attenuates insulin resistance, inflammation and hepatic lipid accumulation in NASH. [35][36][37][38] Although some clinical trials on the treatment of NASH with small molecule inhibitors of ASK1 have not reached definitive endpoints yet, the current efforts of the researchers to treat NASH and its related complications by interfering with ASK1 have never been stopped. 31,32 Collectively, our findings provide new insight into the mode of action of key negative regulators of NASH as ASK1, thus paving the way for clinical translation of basic discoveries.…”
Section: Discussionmentioning
confidence: 99%
“…Three well-characterized MAPK subfamilies are p38, JNK, and ERK1/2, which are related to NASH development. MAPK can be activated by upstream kinase signals, such as apoptosis signal-regulated kinase 1 and mixed-spectrum kinase 3 31,32 . By contrast, MAPKs are inactivated through direct dephosphorylation of their threonine and tyrosine residues by a set of bispeci c protein tyrosines [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%